Cultural Resources of the Aleutian Region Volume I and II - Stein, Gary C. (the Digital Archaeological Record)
There are many problems inherent in attempting to fully assess the cultural resources of an area such as that encompassed in the boundaries of the Aleut Corporation. While there are many things which bind the area together into a unified whole, there are also many differences which must be taken into consideration. Yet both the differences and the unifying aspects are, in large part, caused by the geographic location and environmental effects of the region upon its inhabitants. Volume II of this report consists of the 411 statements of significance which were filed with the Aleut Corporation's site selection applications for historic sites under Section 14(h)(l) of the Alaska Native Claims Settlement Act. This volume should be utilized in conjunction with sections V and VI of Volume I, discussions of the general description and significance of Aleut historic sites, and the recommendations (purely subjective) made concerning their management.